ChemInform Abstract: anti‐Diastereoselective Synthesis of CF3‐Containing Spirooxazolines and Spirooxazines via Regiospecific Trifluoromethylative Spirocyclization by Photoredox Catalysis. Issue 49 (December 2015) - Noto, Naoki; Miyazawa, Kazuki; Koike, Takashi; Akita, Munetaka
Abstract: Starting from cyclic alkenes bearing an amide tether the title reaction provides trifluoromethylated spirooxazolines or spirooxazines in moderate to high yields and with moderate to high anti‐diastereoselectivity.